Stormy onset with prolonged loss of consciousness in benign childhood epilepsy with occipital paroxysms. Issue 1 (January 1992) - Kivity, S; Lerman, P
Abstract : In nine of 62 children with benign occipital epilepsy (BOE) the onset was stormy and alarming. The first and often only seizure was characterised by prolonged loss of consciousness lasting up to 12 hours, suggesting an acute cerebral insult. In all but one case there was a tonic aversion either of eyes alone or of both head and eyes which was interpreted as conjugate deviation. The other accompanying ictal motor phenomena were either partial or generalised convulsions. In five patients the seizure was heralded by a headache, and in five cases was accompanied by vomiting. The seizure began with visual symptoms in only one patient. The seizure occurred while awake in seven and during sleep in two. The age at onset was from 3 1/4 to 10 years. Interictal EEGs showed occipital discharges typical of BOE, and the clinical course was benign. In four cases a few partial or complex partial seizures recurred during subsequent anticonvulsant therapy, but in five cases seizures never recurred. Anticonvulsants were discontinued in five patients who remained free from seizures for one to 11 1/2 years after withdrawal of treatment. Sudden coma in a child associated with focal features such as tonic deviation of the head or eyes or both may represent a benign seizure disorder.